Caracterização morfológica e molecular de acessos de melão coletados no nordeste brasileiro - Dantas, Ana Carolina de Assis (Universidade Federal Rural do Semi-Árido, 2011)
The melon plant is distributed worldwide and is the kind that has the highest phenotypic variability of the genus, especially observed in its fruit. There is great variability which consists an important source of germplasm for genetic improvement programs. Therefore, the knowledge of the genetic variability of vegetable species and how it distributes itself, provides the rational and sustainable use of genetic resources. The objective of the present study was to do a morphological and molecular characterization of accessions of melon plant collected in brazilian northeastern. Were evaluated 40 accesses and three commercial cultivars in a trial conducted in randomized complete block with two repetitions in Mossoró-RN. The morphological characterization was performed through 17 descriptors, one of the seed, fourteen of fruit and two of the inflorescence. The molecular characterization was performed by RAPD markers using 18 primers and by microsatellite (SSR) with 15 primers synthesized for Cucumis melo. It was verified that the morphological markers, RAPD and SSR were satisfactory to allow the detection of polymorphism among the genotypes evaluated. The grouping methods of Tocher and the hierarchical partially agreed on morphological and molecular characterizations. The RAPD marker was more discriminating in relation to microsatellite by the fact of cluster the accesses in most groups. The germplasm bank of UFERSA has high genetic variability among the accessions.
Morphological and molecular characterization of accesses of melon collected in brazilian northeastern
Keywords: Cucumis melo; recursos genéticos; germoplasma; RAPD; SSR; Cucumis melo; genetic resources; germplasm; RAPD; SSR; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA